Follicular dynamics in Zebu cattle - Viana, João Henrique Moreira; Ferreira, Ademir de Moraes; de Sá, Wanderlei Ferreira; Camargo, Luiz Sérgio de Almeida (Pesquisa Agropecuaria Brasileira, 2000)
The aim of this study was to investigate the follicular dynamics during estrous cycle in Gir breed (Bos indicus) cows. Follicular growth and atresia during estrous cycle were evaluated using a portable ultrasound device. Luteal activity was evaluated by serum progesterone levels. Cycles with two (6.67%), three (60.00%), four (26.67%) and five (6.67%) follicular waves were observed. There was no difference (P > 0.05) in dominant or subordinate follicles growth or atresia rates among follicular waves. The maximum diameter of the ovulatory follicle was higher than the diameter of the other dominant follicles in cycles with four waves, and higher than the diameter of the second dominant follicle in cycles with three waves (P < 0.05). There was no difference (P > 0.05) in estrous cycle length (21.11±1.76 and 22.25±1.71 days) or progesterone levels during diestrous (4.48±1.45 and 5.08±1.40 ng/mL) between cycles with three or four waves. Follicular dynamics in Gir cattle is characterized by a higher incidence of cycles with three or four waves, associated with a low persistence of the dominant follicle.